Natriuretic and vasoactive peptides in pre-eclampsia - Pouta, Anneli, 1961- (Oulu : Oulun yliopisto, 1997)
5 erip.
Abstract.
Väitöskirja
Keywords: Atrial Natriuretic Factor; Endothelin-1; Endothelium; Pre-Eclampsia; Pregnancy; doktorsavhandlingar; väitöskirjat